EVALUASI PENGALAMAN PASIEN DENGAN HIPERTENSI SELAMA PERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT IMELDA PEKERJA INDONESIA MEDAN - Naibaho, Eka Nugraha; Supriadi, Kyoko; Siburian, Christine Handayani; Silitonga, Santo Damerius (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Hypertension often causes no symptoms, while persistently high blood pressure over a long period of time can cause complications. The purpose of the study was to determine the experience of patients with hypertension during treatment in the inpatient ward of Imelda Indonesian Workers Hospital Medan. The type of research conducted in this study is a qualitative research with a descriptive phenomenological approach. This research was carried out in the inpatient ward of Imelda Indonesian Workers Hospital Medan in July-August 2022. Participants in this study were 5 patients with hypertension. Data collection techniques in this study used in-depth interview techniques. The results of the study of participants affected by hypertension varied in their length of suffering from hypertension, between 1 to 7 years. Participants revealed that the initial symptoms felt were dizziness, headache, blurred vision, the presence of objects that seemed to move, stiffness and pain in the back of the neck and weakness. When symptoms occurred, participants did not know if the symptoms they felt were signs of having hypertension. Participants affected by hypertension maintained their daily diet at the beginning of their hypertension, still limiting foods such as coffee, meat, fatty foods, but after a long time they could no longer hold back their appetite so they could no longer limit their daily food. Participants have difficulty when maintaining a diet, namely participants have not been able to keep food from salty, fatty, fried, meat and have not been controlled in maintaining a daily food diet. The experience of participants when receiving hypertension therapy was that at the beginning they were sick, participants were still obedient in taking drugs, but over time the participants were getting bored and even fed up with hypertension drugs so that more people did not take drugs according to the doctor's recommendations that had been given to participants. The changes felt when participants were affected by hypertension were that participants were more limited in time to carry out activities and some even took holidays or leave because they had to be hospitalized because of the high blood pressure experienced by these participants. The support that the participants got was that the participant's family always provided support to the participants and accompanied them until the treatment process was completed.